The Effect of Peer Conference Strategy and Self-Confidence toward the Writing Skill of Recount Text (An Experimental Research on the Grade Eight Students of SMPN 22 Padang) - Gusti Melia; M Zaim; Hamzah Hamzah (Universitas Negeri Padang, 2019)
Writing is one of the important skills that should be mastered by the students. In writing, the students need to express their feeling in a good way and well-organized. In fact, most of students were lack of idea and could not write well-organized in written form. The purpose of this research was to find out the effect of Peer Conference Strategy and students’ self-confidence toward the writing skill of recount text. The sample consists of 64 students. The research data was collected using writing test and self-confidence questionnaires. Data analysis was using t-test and Two Ways ANOVA. The analysis of the research results shows that (1) Peer Conference strategy was effective than expository strategy; (2) Peer Conference strategy was effective to high self-confidence students; (3) Peer Conference strategy was not effective to low self-confidence students; (4) There was an interaction both teaching strategies and self-confidence in writing skill.